Formation of Indonesian Laws Post-2022 Amendment to Law No. 12 of 2011 - Usihen, Min; Anshari, Tunggul; Riyanto, R. Benny; Eko Widiarto, Aan (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to analyze the evolution of legal politics in Indonesia’s legislative framework following the amendment of Law No. 12/2011 through the enactment of Law No. 13/2022. This amendment introduced the omnibus method as an innovative approach to drafting regulations. Employing a qualitative methodology rooted in doctrinal legal research and normative analysis, the study examines legal texts, judicial decisions, and other legislative materials. The methodology emphasizes the analysis of legal principles and norms to ensure alignment with constitutional directives and international legal standards. The findings indicate that the implementation of the omnibus method enhances efficiency in the legislative process by consolidating overlapping regulations into a cohesive legal framework. This approach facilitates efforts to address regulatory overload and promotes greater legal certainty. Nevertheless, the study identifies challenges such as resistance within the legislative process and the necessity for continuous oversight to maximize the benefits of this approach. In conclusion, the enactment of Law No. 13/2022 represents a pivotal advancement toward a more responsive and efficient legislative framework in Indonesia. This research provides a valuable contribution to understanding the political dynamics of legal reform and the broader implications of adopting the omnibus method in the national legislative system.